Water-stable perovskite quantum dots-based FRET nanosensor for the detection of Rhodamine 6G in water, food, and biological samples - Chan, Kok Ken (2022)
The practical application of perovskite quantum dots (QDs) for sensing in the aqueous phase has been restricted by their poor resistance to moisture and oxygen due to their highly ionic characteristic. In this work, we employed silica and phospholipid co-encapsulated water-stable all-inorganic CsPbBr3 QDs as a ratiometric fluorescence resonance energy transfer (FRET)-based fluorescence nanosensor for the detection of Rhodamine 6G (R6G) in food, water, and biological samples. The nanosensor on its own exhibits a strong green emission signal at 518 nm. However, in the presence of R6G, the original fluorescence signal at 518 nm decreases while a new emission peak at 565 nm increases, accordingly, indicating a typical ratiometric fluorescence relationship. The fluorescence intensity ratio (I565/I518) was found to be linearly correlated to the concentration of R6G present. The proposed R6G nanosensor has a linear operating range of 0 – 10 g/mL and a detection limit of 0.01 g/mL. In addition, the proposed nanosensor displayed good selectivity towards R6G when tested with other color additives and was also able to detect R6G in tap water, food, and biological samples that contain complex interfering background species. Overall, this work opens a new avenue for water-stable perovskite quantum dots for aqueous-phase sensing applications.